The efficacy of mosonia burkeana, moringa oleifera and trichoderma harzianum on tomato soil-borne fungal pathogens fusarium oxysporum and rhizoctonia solani under in vitro and in vivo conditions - Hlokwe, Mapula Tshepo Pertunia . (My University, 2018)
Tomato is second most cultivated crop globally and in South Africa it is planted by both commercial and smallholder farmers. However, the crop is susceptible to a number of diseases including those caused by fungal pathogens. Fusarium wilt caused by Fusarium oxysporum f. sp. lycopersici and seedling damping-off caused by Rhizoctonia solani, are known to cause serious yield loss in tomato production. Their management is mainly based on the application of synthetic fungicides and cultural practices. However, both methods have limitations which result in their inefficiency. Synthetic fungicides also have negative impact on the environment and human health. The ability of fungal pathogens to develop resistance to fungicides has also resulted in their reduced application. These challenges have led to a need to identify novel methods using plant extracts and biological control agents which can be used to manage these diseases. The objectives of this study were therefore to, firstly determine the efficacy of both plant extracts on mycelial growth of F. oxysporum f. sp. lycopersici and R. solani under laboratory conditions and secondly, to evaluate the effectiveness of both plant extracts as well as antagonistic fungi Trichoderma harzianum against Fusarium wilt and damping-off of tomato under greenhouse conditions. Food poisoning assay was used to investigate the efficacy of M. burkeana and M. oleifera extracts in vitro. Six (0, 2, 4, 6, 8, 10 g/ml) treatments were arranged in a completely randomised design and replicated four times. After 7 days of incubation at 25 °C, radial growth colony was measured. For the greenhouse xp im nt, Fusa ium wilt was t st d on cv. ‘HTX14’ as th most susc ptibl cultiva whilst seedling damping-off was t st d on cv. ‘Mon y-make ’. Aqu ous xt acts were prepared by decocting different concentrations of M. burkeana (4, 6, 8 g/ml) xiv and M. oleifera (2, 4 and 6 g/ml) in 100 ml of distilled water at 100 °C for 15 minutes then left to cool before filtering and applying as a treatment. Trichoderma harzianum as a treatment was applied 7 days after inoculating the soil-borne pathogens. In-vitro M. burkeana treatments concentrations had the highest mycelia growth suppression against both F. oxysporum f. sp. lycopersici at 10 g/ml (76 %) whilst suppression on R. solani was at 8 g/ml (71 %) relative to control. Moringa oleifera xt acts’ highest pathogen suppression for both F. oxysporum f. sp. lycopersici and R. solani were respectively 35 % and 60 % relative to control at concentration 6 g/ml. Under greenhouse conditions shoot disease severity had highest suppression at 0.6 g/ml of M. burkeana and 0.4 g/ml of M. oleifera treatment concentrations resulting to 32 and 49 % relative to control. Whereas, treatment 0.8 g/ml of M. burkeana and 0.4 g/ml of M. oleifera suppressed stem and root discoloration by 39 and 54 % respectively. Trichoderma harzianum significantly (P ≤ 0.05) reduced shoot severity and root and stem discolouration contributing the highest suppression of 49 % relative to control. In damping-off treatments, both plant extracts and T. harzianum also significantly duc d (P ≤ 0.05) pre- and post-emergence damping-off incidence with M.burkeana recording the highest suppression at 78 % followed by M. oleifera at 64 %. Trichoderma harzianum reduced incidence of damping-off by 60 % relative to untreated control on both M. burkeana and M. oleifera experiments. The results of this study showed that M. burkeana, M. oleifera extracts and T. harzianum can be highly suppressive to both tested plant diseases. However, further studies should be conducted to determine their mode of action, application method and their effect on other soil microorganisms. Keywords: Damping-off, Fusarium wilt, Plant extracts, T. harzianum, Tomato plant
Thesis (M.Sc. (Agriculture)) --University of Limpopo, 2018
Keywords: Damping-off; Fusarium wilt; Plant extracts; T. harsianum; Tomato plant; Fungal diseases of plants - Climatic factors; Fusarium wilt of tomato.